People’s perception on parasitic plants : helping humans, harming plants? - Rana, Santosh Kumar; Rana, Hum Kala (International Journal of Biological Research, 2016)
Parasitic plants have a rich ethnobotanical heritage in Nepal. They are harvested for use in medicine, traded as material and invoked during a variety of rituals by practitioners from the low plains to the high Himalayas. However in spite of their local importance, these plant species have received little attention from ethno-biologists due to their unique, often misunderstood, biology. This study seeks to expand the current ethnobotanical knowledge by not only documenting Nepal’s parasitic flora but by also providing insight into how these plants are used and perceived in Nepal’s biologically and culturally diverse environment. Ethnobotanical data for this research was collected using the Participatory Rural Appraisal (PRA) and Rapid Rural Appraisal (RRA) methods among 52 respondents from different ethnic groups of Nepal (4 districts). A total of 20 plants species from five parasitic families were recorded and identified as ethnobotanical uses. They are 13 species of Mistletoe, 3 species of Dodder with 1 variety, 2 species in Balanophoraceae and 1 species in Orobanchaceae. The perceived knowledge of indigenous people led to the hypothesis Doctrine of Signature. With this information, Nepal’s burgeoning state can begin targeting and managing these plant species through agricultural, community forestry and conservation policy.